In vitro screening of extracts from 38 marine animal resources for novel cosmeceutical activities - Seung Tae Im; Yebin Jang; Subin Park; Haeun Mun; Dong Sam Kim; Dae-Sung Lee; Jeong-Min Lee; Mi-Jin Yim; Ji-Yul Kim; Hyun-Soo Kim; Seok-Chun Ko; Won-Kyo Jung; et al. (Fisheries and Aquatic Sciences, 2022)
Marine resources have various biological activities and their constituents are more novel than those of land organisms. Several biologically active constituents have been found in marine organisms. Recently, many studies have reported that marine animals (MAs) can be used as functional ingredients in functional foods or nutraceutical due to their health benefits. However, no studies have extensively investigated the cosmeceutical activities of MAs extracts. Here, 70% ethanol extracts of 38 MAs were investigated for their activities of whitening and anti-aging properties for use as materials in novel cosmeceuticals. Anti-aging activities were determined by skin aging-related enzyme activities (anti-collagenase, anti-elastase, anti-hyaluronidase) and whitening activities (anti-tyrosinase, anti-3,4-dihydroxyl-L-phenylalanine [DOPA] oxidation) evaluated by colorimetric method. Among the 38 MAs, we found that Urechis unicinctus and Petrosia corticata extracts showed the strongest inhibitory effects against tyrosinase and DOPA oxidation, respectively. Our results additionally showed that Protankyra bidentata extract might provide a major source of anti-hyaluronidase and anti-elastase; meanwhile, anti-collagenase effects were similar in most MAs. Overall, these results suggest that extracts of marine animals have potential as a tyrosinase, collagenase, elastase, and hyaluronidase inhibitors. Taken together, MA resources could be considered as a novel cosmeceutical agent to be applied in cosmetic industry.